Il carattere dialogico di ragione e fede secondo Joseph Ratzinger - Benedetto XVI - Frývaldský, Pavel (Bogoslovni vestnik, 2023)
The article presents the dialogical conception of Christian faith and reason in the work of Joseph Ratzinger - Benedict XVI. The German theologian engages in the ongoing debate in twentieth-century Germany about the role of philosophy in theological discourse and presents his conception on the basis of a classical synthesis of Greek thought and the biblical message in ancient and medieval Christianity. A Christological conception of truth and a relational understanding of the person of man and his reason enables one to overcome the dualistic relationship between faith and reason and offers still valid perspectives for a mutual dialogue between theology and philosophy.
Keywords: Benedikt; biblical faith; biblična vera; dialog; dialogo; dialogue; fede biblica; metafisica; metafizika; metaphysics; personalism; personalismo; personalizem